Vasculitis with panniculitis following botulinum toxin A injection for cosmetic use - Nastaran Namazi; Reza M. Robati; Sahar Dadkhahfar; Anoush Shafiee; Farahnaz Bidari-Zerehpoush (Mattioli1885, 2016)
Botulinum toxin A injection is performed most frequently for facial rejuvenation all over the world. Some bizarre and severe side effects have been reported after botulinum toxin A injection. Herein, we present a case of vasculitis with panniculitis after a patient underwent a cosmetic procedure that included injection of purported botulinum toxin A.